2008
DOI: 10.1210/jc.2008-0481
|View full text |Cite
|
Sign up to set email alerts
|

The Decline in Hip Bone Density after Gastric Bypass Surgery Is Associated with Extent of Weight Loss

Abstract: After Roux-en-Y gastric bypass, there was evidence of calcium and vitamin D malabsorption. Bone turnover increased, and hip bone density rapidly declined. The decline in hip BMD was strongly associated with weight loss itself. Vigilance for nutritional deficiencies and bone loss in patients both before and after bariatric surgery is crucial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
246
4
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(297 citation statements)
references
References 36 publications
28
246
4
19
Order By: Relevance
“…Fleischer and cols. (18) reported that the extension of weight loss is directly associated with the intensity of the reduction in BMD at all sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fleischer and cols. (18) reported that the extension of weight loss is directly associated with the intensity of the reduction in BMD at all sites.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hyperparathyroidism may reach 58% in patients after RYBG (14)(15)18). Furthermore, patients submitted to bariatric surgery may present chronic magnesium depletions which also leads to a blunt in PTH secretion, osteoporosis and vitamin D deficiency (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] In addition, the extent of bone loss varies with each study and none have been carried out in a sufficient number of patients to allow a firm conclusion. [19][20][21] Thus, the aim of this review is to summarize the current state of knowledge regarding the relationship between bariatric operations and bone metabolism, to understand the specific mechanisms of action and to suggest further research studies.…”
Section: Introductionmentioning
confidence: 99%
“…Serum calcium, however, is an unreliable marker, as although total body calcium maybe reduced, serum calcium is often maintained by the action of PTH. Bone turnover can also be measured using markers such as osteocalcin, which in surgically induced weight loss is significantly raised [27,28].…”
Section: Methods For Assessing Metabolic Bone Changesmentioning
confidence: 99%